CeCl3 center dot 7H(2)O-NaI promoted regioselective sulfenylation of indoles with sulfonylhydrazides - Nookaraju, U.; Begari, Eeshwaraiah; Yetra, Ravikiran Reddy; Kumar, Pradeep (Chemistryselect, 2016)
A simple and highly efficient method has been developed for the regioselective sulfenylation of a wide variety of indoles with alkyl and aryl sulfonylhydrazides as a sulphur source and CeCl3 center dot 7H(2)O-Nal as an inexpensive and readily available reagent system. This method involves the breaking of sulfur-oxygen and sulfur-nitrogen bonds and making of carbon-sulfur bond. The method provides high yields of the products with enhanced regioselectivity. We studied the reactivity of various electron rich and electron deficient indoles towards the sulfe-nylation reaction. The indoles containing electron donating group reacts fast towards the sulfenylation reaction as compared to the indoles containing electron withdrawing groups. More over functional groups like alkoxy, aryloxy, bromo, nitro, cyano, ester, were well tolerated under the established reaction conditions. We also proposed a plausible mechanism for this transformation. The experimental simplicity and environmentally benign nature of the reagent system makes this method an attractive alternative to established methods.